Pre-existing Comorbidity Burden and Patient Perceived Stroke Impact. Issue 3 (April 2021) - Sewell, Katherine; Tse, Tamara; Harris, Elizabeth; Matyas, Thomas; Churilov, Leonid; Ma, Henry; Davis, Stephen M; Donnan, Geoffrey A; Carey, Leeanne M
Background: Pre-existing comorbidities can compromise recovery post-stroke. However, the association between comorbidity burden and patient-rated perceived impact has not been systematically investigated. To date, only observer-rated outcome measures of function, disability, and dependence have been used, despite the complexity of the impact of stroke on an individual. Aim: Our aim was to explore the association between comorbidity burden and patient-rated perceived impact and overall recovery, within the first-year post-stroke, after adjusting for stroke severity, age, and sex. Methods: The sample comprised 177 stroke survivors from 18 hospitals throughout Australia and New Zealand. Comorbidity burden was calculated using the Charlson Comorbidity Index. Perceived impact and recovery were measured by the Stroke Impact Scale index and Stroke Impact Scale overall recovery scale. Quantile regression models were applied to investigate the association between comorbidity burden and perceived impact and recovery. Results: Significant negative associations between the Charlson Comorbidity Index and the Stroke Impact Scale index were found at three months. At the .25 quantile, a one-point increase on the Charlson Comorbidity Index was associated with 6.80-points decrease on the Stroke Impact Scale index (95%CI: −11.26, −2.34; p = .003). At the median and .75 quantile, a one-point increase on the Charlson Comorbidity Index was associated, respectively, with 3.58-points decrease (95%CI: −5.62, −1.54; p = .001) and 1.76-points decrease (95%CI: −2.80, −0.73; p = .001) on the Stroke Impact Scale index. At 12 months, at the .25 and .75 quantiles, a one-point increase on the Charlson Comorbidity Index was associated, respectively, with 6.47-points decrease (95%CI: −11.05, −1.89; p = .006) and 1.26-points decrease (95%CI: −2.11, −0.42; p = .004) on the Stroke Impact Scale index. For the Stroke Impact Scale overall recovery measure, significant negative associations were found only at the median at three months and at the .75 quantile at 12 months. Conclusion: Comorbidity burden is independently associated with patient-rated perceived impact within the first-year post-stroke. The addition of patient-rated impact measures in personalized rehabilitation may enhance the use of conventional observer-rated outcome measures.